(untitled) (Sociologisk Forskning, 1998)
The limited freedom of tastes - on the culture industry’s power over its audiences Taking Horkheimer and Adorno’s Dialectic of Enlightenment as the main point of departure, this article deals with the question of the culture industry’s power to determine the cultural taste of audiences. Through an overview of literature within foremost political economy (especially about cultural imperialism) and cultural studies (focusing on the meaning creating processes of audiences), a re-evaluation of Horkheimer and Adorno’s original thesis is made. The article concludes that many of the core ideas of the Frankfurt school are still relevant to apply within cultural sociology and media studies. The culture industry’s power over its audiences lies in its potential to make the cultural content accessible to lots of people through the repetition and the successive transition of generic conventions. However, these ideas must be made more dynamic and less elitistic. This means that audiences must be considered as active producers of meaning, situated in specific sociocultural contexts. Without this revision, the perspective of Horkheimer and Adorno is far too rigid to make any good sense within the reflexive cultural climate of late modernity.